Effects of simulated domestic and international air travel on sleep, performance, and recovery for team sports - Fowler, P.; Duffield, R.; Vaile, J. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The present study examined effects of simulated air travel on physical performance. In a randomized crossover design, 10 physically active males completed a simulated 5-h domestic flight (DOM), 24-h simulated international travel (INT), and a control trial (CON). The mild hypoxia, seating arrangements, and activity levels typically encountered during air travel were simulated in a normobaric, hypoxic altitude room. Physical performance was assessed in the afternoon of the day before (D - 1 PM) and in the morning (D + 1 AM) and afternoon (D + 1 PM) of the day following each trial. Mood states and physiological and perceptual responses to exercise were also examined at these time points, while sleep quantity and quality were monitored throughout each condition. Sleep quantity and quality were significantly reduced during INT compared with CON and DOM (P < 0.01). Yo-Yo Intermittent Recovery level 1 test performance was significantly reduced at D + 1 PM following INT compared with CON and DOM (P < 0.01), where performance remained unchanged (P > 0.05). Compared with baseline, physiological and perceptual responses to exercise, and mood states were exacerbated following the INT trial (P < 0.05). Attenuated intermittent-sprint performance following simulated international air travel may be due to sleep disruption during travel and the subsequent exacerbated physiological and perceptual markers of fatigue.